Impact of Orthodontic Forces on Plasma Levels of Markers of Bone Turnover and Inflammation in a Rat Model of Buccal Expansion - Danz, Jan C.; Kantarci, Alpdogan; Bornstein, Michael M.; Katsaros, Christos; Stavropoulos, Andreas (Frontiers in Physiology, 2021)
Plasma levels of protein analytes might be markers to predict and monitor the kinetics of bone and tissue remodeling, including maximization of orthodontic treatment stability. They could help predict/prevent and/or diagnose possible adverse effects such as bone dehiscences, gingival recession, or root resorption. The objective of this study was to measure plasma levels of markers of bone turnover and inflammation during orthodontic force application in a rat model of orthodontic expansion. Two different orthodontic forces for bilateral buccal expansion of the maxillary arches around second and third molars were applied in 10 rats equally distributed in low-force (LF) or conventional force (CF) groups. Four rats served as the control group. Blood samples were collected at days 0, 1, 2, 3, 6, 13, 21, and 58. Longitudinal concentrations of osteoprotegerin (OPG), soluble receptor activator of nuclear factor kappaB ligand (sRANKL), interleukin 4 (IL-4), interleukin 6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor α (TNF), and parathyroid hormone (PTH) were determined in blood samples by a multiplex immunoassay. CF and LF resulted in a significantly maxillary skeletal expansion while the CF group demonstrated significantly higher expansion than the LF group in the long term. Bone turnover demonstrated a two-phase response. During the "early phase" (up to 6 days of force application), LF resulted in more sRANKL expression and increased sRANKL/OPG ratio than the CF and control animals. There was a parallel increase in PTH levels in the early phase in response to LF. During the "late phase" (6-58 days), the markers of bone turnover were stable in both groups. IL-4, IL-6, and IL-10 levels did not significantly change the test groups throughout the study. These results suggest that maxillary expansion in response to different orthodontic forces follows different phases of bone turnover that may be force-specific.